A new method of international education: Using a consulting model to build social work skills in Chile. (November 2018) - Marchant, Alissa Anne; Germak, Katherine; Berzin, Stephanie
International experiences in social work education have become more common in the last few decades. The literature has shown these experiences to improve students' cultural competency, intercultural communication, and work habits. The literature focuses on diffused learning experiences, where students visit and hear from local agencies. This article offers a consulting model as an alternative experiential learning method. Master's level students at the Boston College School of Social Work report improved cultural competence and also the development of hard skills, such as collaboration, that will transfer to future social work employment.